2014
DOI: 10.1111/ijs.12269
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Ischemic and Hemorrhagic Recurrence Rates among Race-Ethnic Groups in the PRoFESS Secondary Stroke Prevention Trial

Abstract: We found a significant difference in myocardial infarction and symptomatic intracerebral hemorrhage recurrence among different race-ethnic groups. The risk of recurrent ischemic and hemorrhagic stroke was greater in Asians with high blood pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…The risk of ICH was significantly higher in this group, especially in individuals with hypertension (systolic BP > 150) compared to Caucasians. 30 Similarly, the risk of warfarinrelated ICH was four times higher in Far Eastern patients compared to Caucasians, 31 in patients treated for atrial fibrillation in a large cohort study from California. In an interesting comparison of stroke etiology in long-term residents in Hawaii, similar trends were evident.…”
Section: Discussionmentioning
confidence: 98%
“…The risk of ICH was significantly higher in this group, especially in individuals with hypertension (systolic BP > 150) compared to Caucasians. 30 Similarly, the risk of warfarinrelated ICH was four times higher in Far Eastern patients compared to Caucasians, 31 in patients treated for atrial fibrillation in a large cohort study from California. In an interesting comparison of stroke etiology in long-term residents in Hawaii, similar trends were evident.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to the ethnic differences in the risk of AF, the Reasons for Geographic and Racial Differences in Stroke (REGARDS) investigators found there are ethnic differences in the incidence of stroke. It has been shown that there is a significant difference in myocardial infarction and symptomatic intracerebral haemorrhage recurrence among different ethnic groups [18] , [19] , [20] , [21] . As hypertension and diabetes are highly prevalent among Asian Indian population, it is expected that this significantly contributes to the higher rate of strokes and heart attacks in India [22] .…”
Section: Discussionmentioning
confidence: 99%
“…Several more recent meta-analyses showed that, compared with aspirin, cilostazol not only had similar or even slight better therapeutic effects in stroke prevention, but also had a significant reduction in the hemorrhagic stroke [ 18 21 , 26 ]. It has been reported that Asians have a higher risk of recurrent ischemic and hemorrhagic stroke in the secondary stroke prevention phase [ 22 ]. Interestingly, a few studies and one recent meta-analysis revealed that cilostazol also provided a protective effect in the secondary prevention of the chronic phase of ischemic stroke in Asian patients [ 16 , 20 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, ABI less than 0.90 was considered as evidence of PAD [ 18 20 ]. Absence of PAD was defined as ABI between 0.90 and 1.30 [ 21 , 22 ]. Individuals with ABI greater than 1.30 were excluded, because this indicates poorly compressible leg arteries and inability to gauge arterial perfusion accurately [ 21 , 23 ].…”
Section: Methodsmentioning
confidence: 99%